2019
DOI: 10.1002/hed.25890
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of re‐irradiation for recurrent or second primary head and neck cancer: A multi‐institutional study of AIRO—Head and Neck working group

Abstract: Background To report the long‐term outcome of patients undergoing re‐irradiation (re‐RT) for a recurrent or second primary head and neck cancer (RSPHNCs) in seven Italian tertiary centers, while testing the Multi‐Institution Reirradation (MIRI) recursive partitioning analysis (RPA) recently published. Methods We retrospectively analyzed 159 patients. Prognostic factors for overall survival (OS) selected by a random forest model were included in a multivariable Cox analysis. To externally validate MIRI RPA, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…With the development of modern radiation techniques, such as 3-dimensional conformal radiotherapy (3D-CRT) or intensify modulated radiotherapy (IMRT), reirradiation is applied for rHNSC after EBRT. Reirradiation using EBRT with or without chemotherapy improved the local control rates in half of the patients and long-term survival in selected patients ( 19 , 20 ). EBRT as a salvage option is promising for rHNSC in the previously irradiated area although it still poses a great challenge as it is hard to deliver sufficient doses to the targets while sparing the normal tissues, especially for tumors previously treated with full doses.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern radiation techniques, such as 3-dimensional conformal radiotherapy (3D-CRT) or intensify modulated radiotherapy (IMRT), reirradiation is applied for rHNSC after EBRT. Reirradiation using EBRT with or without chemotherapy improved the local control rates in half of the patients and long-term survival in selected patients ( 19 , 20 ). EBRT as a salvage option is promising for rHNSC in the previously irradiated area although it still poses a great challenge as it is hard to deliver sufficient doses to the targets while sparing the normal tissues, especially for tumors previously treated with full doses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mallik et al reported 47 submandibular gland cancers, mostly ACCs, with a 5-year DFS of 71.8%, 12.8% (n = 6) of loco-regional failure, and 12.8% (n = 6) of development of distant metastases. Compared to the past, availability of new effective systemic treatments (e.g., androgen deprivation therapy, ADT; anti-HER2 monoclonal antibody), improvement in the re-irradiation (reRT) [19] techniques and the opening of heavy ions facility in Italy in 2011 have offered new therapeutic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to IMRT, most of the experience in literature refers to mixed series where the number of SGCs is significantly lower than pharyngeal or laryngeal squamous cell carcinoma cases [19,43,44]. Recently, Orlandi et al analyzed reRT outcomes on a cohort of 159 patients, of which 71 (45%) were not squamous cell carcinomas (in particular, 25 (16%) were ACC and 8 (5%) were affected by SGCs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes also correlate with the site of recurrence with nasopharyngeal and laryngeal cancer revealing a better prognosis [23,[28][29][30][31][32]. Generally, nasopharyngeal tumors have a higher radiosensitivity which could be also an explanation for its favorable prognosis with Re-RT.…”
Section: Anatomical Sitementioning
confidence: 98%